The International Law Commission is 70 … Staying with the Old and Playing with the New? Reflections on the Work of the Commission during its Commemorative Year - Tladi, Dire (South African Yearbook of International Law, 2020)
In 2018, the International Law Commission (ILC) celebrated its 70th anniversary. In this commemorative year, the Commission had a number of topics on its agenda. It completed, on second reading, draft conclusions on the identification of customary international law and draft conclusions on subsequent practice in relation to treaty interpretation. These two topics are of particular importance because of their systemic influence on international law. The Commission also completed, on first reading, the draft guidelines on the protection of the atmosphere and the draft guidelines on the provisional application of treaties. Other topics considered by the Commission include peremptory norms of general international law (jus cogens), immunity of state officials from foreign criminal jurisdiction and the protection of the environment in relation to armed conflict. The Commission also considered the topic on succession of states in respect of state responsibility. In other decisions, the Commission placed on its agenda the topic of general principles of law. The Commission also included two topics on its long-term programme of work, namely universal criminal jurisdiction and sea-level rise in international law. The topics on the agenda of the Commission reflect the broad spectrum of issues, ranging from classical international law topics such as customary international law, treaties and jus cogens to more contemporary topics such as sea-level rise and the protection of the atmosphere. This range suggests that the Commission is attempting to integrate the new and the old into its work.